PENGARUH PENGELOLAAN SISTEM INFORMASI MANAJEMEN TERHADAP TUGAS GURU SMK NEGERI SE-KABUPATEN MALANG - Tri Firman Syah (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2020)
The existence of the role and function of teachers is one of the most important factors in education, both formal and informal education. Problems faced by teachers in Indonesia are: (1) the problem of teacher quality; (2) the problem of the number of teachers who are still lacking; (3) the problem of teacher distribution; (4) the problem of teacher welfare. Data from PSG Rayon 115 of 2012 and Teacher Competency Test (UKG) from 2012 to 2015 shows that there are still many teachers in  Malang Regency who have not been able to develop their productivity in teaching. Education in the global era requires the management of modern and professional education with an educational nuance. Educational institutions are expected to be able to realize their role effectively with excellence in leadership, staff, teaching and learning processes, staff development, curriculum, goals and expectations, school climate, self-assessment, communication, and parent / community involvement. Management Information Systems have a role in improving the work of teachers because it can accelerate the work of teachers to deliver material to students making learning tools and student reports. Management information system cannot be separated from the support of facilities and infrastructure used in conveying information and the process of delivering information. The application of a MIS, makes school management neat so as to improve the performance of employees and teachers. In addition the school also cooperates with the company by providing laboratory equipment, instructors, and teacher training for work standards and standards of learning materials needed by the company. So that it can improve the task of the teacher in providing subject matter that has been adapted between the national curriculum and the company.